2012
DOI: 10.1108/01140581211283896
|View full text |Cite
|
Sign up to set email alerts
|

Gender, operational efficiency, population density and the performance of mirofinancing institutions

Abstract: PurposeThe purpose of this research is to investigate the effect of operational efficiency, gender of the borrowers and the population density on the performance of microfinancing institutions that play a significant role in alleviating poverty in developing countries.Design/methodology/approachA model showing the relationships among the variables is first proposed based on the hypotheses developed in the literature review. Then the model is tested with empirical data using multiple regression and path analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, two recent global studies have found that women borrowers are better compared to men. Nanayakkara and Mia (2012) analysed 234 MFIs across 63 countries and found that the percentage of female borrowers has a significant effect on the performance of MFIs. From a sample of 350 MFIs located in 70 countries, D 'Espallier et al (2011) found that the repayment record of females is better than that of their male counterparts after controlling for a number of other variables.…”
Section: Characteristics Of the Loanmentioning
confidence: 99%
“…However, two recent global studies have found that women borrowers are better compared to men. Nanayakkara and Mia (2012) analysed 234 MFIs across 63 countries and found that the percentage of female borrowers has a significant effect on the performance of MFIs. From a sample of 350 MFIs located in 70 countries, D 'Espallier et al (2011) found that the repayment record of females is better than that of their male counterparts after controlling for a number of other variables.…”
Section: Characteristics Of the Loanmentioning
confidence: 99%
“…Further studies are also required in each of the clusters considering that some terms relevant to microfinance banking in other countries such as 'gender' (Nanayakkara, 2012) were missing from the selected literature. New studies must assess issues besides these three main thematic areas identified in the literature and comprehensively understand the causal linkages between the terms in each cluster.…”
Section: Discussionmentioning
confidence: 99%